Imaginal retraining reduces alcohol craving in problem drinkers: A randomized controlled trial. (September 2019) - Moritz, Steffen; Paulus, Alia Marie; Hottenrott, Birgit; Weierstall, Roland; Gallinat, Jürgen; Kühn, Simone
Abstract: Background and objectives: Retraining, a psychological intervention derived from the approach-avoidance paradigm, has yielded mixed results for the treatment of alcohol use disorder as well as other forms of addiction. The present study investigated the efficacy of an imaginal variant of retraining that allowed greater personalization of the content. Methods: Within the framework of a randomized controlled trial (RCT), 84 individuals with self-reported alcohol-related problems were recruited over the Internet and allocated to either imaginal retraining (treatment manual dispatched as a pdf-file via email) or a wait-list control group (with care-as-usual). The intervention period was four weeks. Alcohol craving, as measured with a visual analogue scale (VAS), served as the primary outcome. Other emotional (e.g. self-esteem) and drinking-related variables served as secondary outcomes. Results: Both per-protocol (PP) and intention-to-treat (ITT) analyses showed that imaginal retraining led to a significant reduction in alcohol craving compared to the control group at a large effect size. Self-esteem improved in the retraining condition relative to controls in the PP and one of the ITT analyses; 75% of the individuals in the treatment group reported less alcohol consumption in the treatment period, whereas drinking behavior remained essentially unchanged in the control group ( p  < .001) (the trial was registered at the German Clinical Trials Register, DRKS00015319). Limitations: Whether the effects of imaginal retraining are sustained over time needs to be established. Attrition was significantly higher in the retraining group (40.5%) than in the control group (16.7%). Designs with an active control condition are needed as well as dismantling studies to explore which of the treatment's multiple components best predicts improvement. Future studies should verify participants' alcohol consumption levels using objective measures. Conclusion: Imaginal retraining led to significant effects on the reduction of alcohol craving. Highlights: Effects of retraining for alcohol use disorder are promising but weak. This study examined the effectiveness of imaginal retraining. Imaginal retraining led to a significant reduction in craving compared controls. 75% in the intervention goup reported less alcohol consumption.